2018
DOI: 10.1007/s11162-018-9511-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Attraction, Retention and Completion for Aboriginal and Torres Strait Islander Higher Degree Research Students: A Systematic Review to Inform Future Research Directions

Abstract: While numbers of Aboriginal and Torres Strait Islander Peoples' (hereafter Indigenous Peoples) completing undergraduate degrees has improved markedly in recent years, Indigenous Peoples remain under-represented in HDR programmes which limits progression into academic careers. This paper explores factors affecting Indigenous Peoples' commencement and completion of higher degree research (HDR) programmes. The research was undertaken at a large, multicampus, metropolitan Australian university and involved a quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Echoing the findings of this study, previous research has recommended that initiatives and strategies such as mentorship programs, increasing student support, and culturally inclusive curricula and programming are important for Indigenous students and faculty (Canel-Çınarbaş & Yohani, 2019; Elston et al, 2013; Hutchings et al, 2019). Like the participants in this study, Indigenous Australian scholars in Elston’s et al (2013) study identified a dedicated space for Indigenous peoples as important.…”
Section: Discussionmentioning
confidence: 57%
“…Echoing the findings of this study, previous research has recommended that initiatives and strategies such as mentorship programs, increasing student support, and culturally inclusive curricula and programming are important for Indigenous students and faculty (Canel-Çınarbaş & Yohani, 2019; Elston et al, 2013; Hutchings et al, 2019). Like the participants in this study, Indigenous Australian scholars in Elston’s et al (2013) study identified a dedicated space for Indigenous peoples as important.…”
Section: Discussionmentioning
confidence: 57%
“…Inclusion criteria in order of priority will be as follows: Indigenous authored or co-authored. This will be determined as best as possible based on examples found in other published reviews [ 24 , 30 , 31 ] where Indigenous authorship is identified, our own knowledge of the scholars/writers, the writers’ own self-declarations, and any further inquiry we need to do. Other authors, where the documents meet the other criteria listed here.…”
Section: Methodsmentioning
confidence: 99%
“…Indigenous authored or co-authored. This will be determined as best as possible based on examples found in other published reviews [24,30,31] where Indigenous authorship is identified, our own knowledge of the scholars/writers, the writers' own self-declarations, and any further inquiry we need to do. The centre of the model refers to the interconnection between mental, physical, spiritual, and emotional behaviour-purpose, hope, meaning, and belonging.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…This clearly disadvantages the health professions workforce who do not typically follow an honours or science pathway and may have little or no have formal research education 6 . The Aboriginal and Torres Strait Islander workforce experiences further inequity due to a systemic failure to recognise their cultural expertise 20 . Concurrently, this rural and remote health research workforce also comes with substantial other postgraduate education or workforce experiences, and firsthand lived knowledge about rural and remote settings and communities.…”
Section: The Current State Of Formal Research Educationmentioning
confidence: 99%
“…6 The Aboriginal and Torres Strait Islander workforce experiences further inequity due to a systemic failure to recognise their cultural expertise. 20 Concurrently, this rural and remote health research workforce also comes with substantial other postgraduate education or workforce experiences, and firsthand lived knowledge about rural and remote settings and communities. In their national report on the state of the Australian research training system, McGagh, Marsh 17 have noted that prior work experiences are not adequately recognised and could be better integrated to provide a more holistic picture of academic preparedness.…”
Section: Which Includes Both Masters By Research and Phds A Masters Bymentioning
confidence: 99%